How are Attitudes Toward COVID-19 Associated with Traveler Behavior During the Pandemic? - Denise Capasso da Silva; Sara Khoeini; Deborah Salon; Matthew W. Conway; Rishabh S. Chauhan; Ram M. Pendyala; Ali Shamshiripour; Ehsan Rahimi; Tassio Magassy; Abolfazl (Kouros) Mohammadian; Sybil Derrible (Findings)
This article uses data from the first wave of the COVID Future Panel study to evaluate attitudes towards COVID-19 and their influence on traveler behaviors. An exploratory factor analysis identified two underlying constructs based on the measured attitudes, namely “Concern about Pandemic Response” and “COVID Health Concern.” A cluster analysis based on the factor scores yielded four groups with distinct attitudes. Those primarily concerned about the pandemic response traveled the most using private vehicles, while those equally concerned about the response to the pandemic and the health effects of COVID-19 were found to use personal bicycles and transit the most.